2017
DOI: 10.1021/acs.jpcb.7b02445
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Origin of the Red Solvatochromic Shift of DFHBDI in RNA Spinach

Abstract: Interactions with the environment tune the spectral properties of biological chromophores, e.g., fluorescent proteins. Understanding the relative contribution of the various types of noncovalent interactions in the spectral shifts can provide rational design principles toward developing new fluorescent probes. In this work, we investigate the origin of the red shift in the absorption spectra of the difluoro hydroxybenzylidene dimethyl imidazolinone (DFHBDI) chromophore in RNA spinach as compared to the aqueous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…This suggests that the Chili RNA exclusively binds the DMHBO + chromophore in its protonated state. The bathochromic shift of 20 nm compared to the free phenol likely originates from a combination of π‐stacking and electrostatic interactions . Excitation of the protonated chromophore‐RNA complex is followed by fast deprotonation, which results in the large apparent Stokes shift of 136 nm.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the Chili RNA exclusively binds the DMHBO + chromophore in its protonated state. The bathochromic shift of 20 nm compared to the free phenol likely originates from a combination of π‐stacking and electrostatic interactions . Excitation of the protonated chromophore‐RNA complex is followed by fast deprotonation, which results in the large apparent Stokes shift of 136 nm.…”
Section: Figurementioning
confidence: 99%
“…The bathochromic shift of 20 nm compared to the free phenol likely originates from ac ombination of p-stacking and electrostatic interactions. [26] Excitation of the protonated chromophore-RNA complex is followed by fast deprotonation, which resultsi nt he large apparent Stokes shift of 136 nm. These results suggest that af unctional group of the RNA near the phenola cts as ap rotons huttle.…”
Section: Stokes Shift [Nm]mentioning
confidence: 99%
“…Additionally, CAM-B3LYP's performance is also tested against the SOS-CIS(D) method [104,105] with aug-cc-pVDZ basis set using QCHEM [106]. The latter wavefunction method is known to exhibit good accuracy for excitation energies [107,108] with experimental results. Here, we want to compare its performance with STEOM-DLPNO-CCSD for modeling BODIPY's S 0 → S 1 excitation energy.…”
Section: A Bodipys Chemical Space Designmentioning
confidence: 99%
“…Quantum mechanics/molecular mechanics (QM/MM) point calculations from energy minimized structures have suggested that the presence of SPINACH increases the barrier to rotation of the imidazole group primarily through interaction with the MM environment and not through RNA-induced perturbation to the QM energies 8 . A subsequent study highlighted the role of the electrostatic environment in shifting chromophore vertical excitation energies 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The photophysics of DFHBI bound to SPINACH has been an active area of research 3,79 . When exposed to continuous light at the same illumination level, RNA-bound DFHBI exhibited less photobleaching than EGFP or fluorescein 3 .…”
Section: Introductionmentioning
confidence: 99%